Idea paper: Effects of gonad type and body mass on the time required for sex change in fishes. Issue 4 (8th March 2022) - Tokunaga, Soma; Kadota, Tatsuru; Watanabe, Yuuki Y.; Kuwamura, Tetsuo; Kawabata, Yuuki
Abstract: Sex change is a well‐known phenomenon in teleost fishes, and it takes several days to a few months depending on the species and direction of sex change. However, the underlying factors influencing the time required for sex change ( T S ) remain unclear. Given that the time for producing a new gonad largely determines T S, the gonad type (i.e., whether fish retain the gonad of opposite sex or not [delimited or non‐delimited]) and metabolic rate may affect T S. This study sought to test two hypotheses: (1) the delimited gonad shortens T S and (2) T S scales with mass 0.1−0.2, because the metabolic scaling exponent ( β ) in fishes is 0.8–0.9 and biological times scale with mass 1− β in general. We compiled data on T S for 12 female‐to‐male and 14 male‐to‐female sex‐changing species from the literature. Results of individual examinations of the effects of gonad type and mass were consistent with our hypotheses. However, upon simultaneous examination of the effects of gonad type and mass, these effects became unclear because of their strong multicollinearity. The compiled data for delimited and non‐delimited gonads were biased toward the smaller and larger species, respectively, precluding us from being able to statistically distinguish between these effects. Small species with non‐delimited gonads and large species with delimited gonads exist; however, their T S has not been measured with high temporal resolution thus far. Therefore, additional experiments on these species are required to statistically distinguish between, as well as to better understand, the effects of gonad type and mass on T S . Abstract : Sex change is a well‐known phenomenon in fish; however, the underlying factors that explain the variation in the time required for sex change ( T S ) among species remain unclear. This study collected as many T S datasets as possible from the literature to demonstrate that either gonad type, body mass, or both affect T S . We could not statistically distinguish the effects of these two factors because of their strong multicollinearity; however, we clearly demonstrate which species' T S data are required to solve this problem.